Perceptions and attitudes of cow-calf producers toward emerging technologies and policy issues in the beef cattle industry - Breiner, Sharon Jene' (Kansas State University, 2007)
The proposed U.S. National Animal Identification System (US-NAIS) has generated many concerns among beef cattle producers. The goal of the NAIS is to utilize 48-hour traceback in the event of an animal disease outbreak. The traceback would identify all animals that have had contact with the diseased animal, while linking an animal to its premises of origin. According to the Diffusion of Innovation theory, getting a new idea adopted, even when it has clear advantages, is often very difficult. However, by adopting innovations relatively sooner than others in their system, the theory demonstrates marked benefits for innovators and early adopters, as well as a widening of the socioeconomic gap. In this study beef producer demonstrated understanding, acceptance and adaptability to implement the US-NAIS. Participants for the study were selected in the spring of 2006 from a mailing list of cow-calf producers with more than 100 head of cows. BEEF Magazine provided the mailing list and a random sample of 1,000 producers was selected. The results show a knowledge gap between the proposed system and producer understanding. Producers were also divided on support for the proposed system. When ranking their level of support on a scale of 1 to 6, with 1 being strongly supportive and 6 being strongly opposed, 49% of producers showed some level of support and 48% showed some level of opposition, with a mean of 3.53 (s.d. 1.67). Data also highlights a lack of understanding of the regulations and implementation procedures among producers. The results of this study brought considerable insight into the current practices and perceptions of beef cattle producers, and will be used to develop educational materials to improve their understanding of this proposed program.
Keywords: Electronic Identification; National Animal Identification System; Beef Cattle; Cattle Producer Attitudes; Agriculture, Animal Culture and Nutrition (0475)